INULIN SEBAGAI PREBIOTIK - Azhar, Minda (Lembaga Penelitian Universitas Negeri Padang, 2009)
Inulin is natural polymer belong to a class of carbohydrates. Inulin has effect the best of prebiotic. Inulin is fermented by Bifidobacteria and Lactobacilli quictly and easy. Major product of fermentation is short chain fatty acids (SCFA) and L-laktate. SCFA is an important function of the large intestine. SCFA influence immune function, heart health, cancer prevention. SCFA decrease colonic and faecal pH, so support growth of Lactobacilli and Bifidobacteria, inhibits growth of patogen bacterial. SCFA can influences metabolism of lipid and glucose. Inulin can increase absortion of Ca, Mg and Fe. Key words : inulin, prebiotic, probiotic, SCFA